The Piast castle on Ostrów Tumski island in Wrocław - Chorowska, Małgorzata; Bartz, Wojciech; Caban, Mariusz; Wodejko, Eryk (Archaeologia Historica Polona, 2021)
The article briefly presents the author’s hypothesis of architectural changes in the ducal castle on Ostrów Tumski in Wrocław, which was developed based on the results of architectural studies of the relics of the castle walls uncovered in excavations in 2011–2012 and 2014, in combination with the results of laboratory tests such as petrographic and mineralogical analysis of mortars, 14C analysis of charcoal contained in mortars and extensive analysis of brick dimensions using statistical methods. As a result, a chronological stratification into eight phases from the 12th to 15th centuries is proposed. Absolute dating was addressed through radiocarbon analyses and historical context.